Finding Children’s Creations in the Archives: Methodological Considerations for Scholars - Kuecker, Elliott (Journal of Juvenilia Studies, 2026)
This essay discusses the methodological complications in conducting archival research to locate the cultural productions of children from the past. I argue that the struggle to locate things created by children in archives, which scholars within juvenilia studies and the related field of childhood studies frequently lament, is likely due to the limitations of archives themselves, as well as the bibliographic standards that archives follow in describing their materials. In addition to analysing where these methodological obstacles originate, I also elaborate on archival search strategies specifically for researchers seeking traces of children from the past.